346 Supplementing Ca salts of soybean oil to enhance carcass quality of beef cattle via metabolic imprinting events. (5th December 2019) - Schubach, Kelsey; Cooke, Reinaldo F; Brandão, Alice; Bohnert, David; Marques, Rodrigo
Abstract: This experiment evaluated the effects of supplementing Ca salts of soybean oil (CSSO) at 2 mo of age via creep-feeding, upon weaning at 6 months of age, or no CSSO supplementation on growth and carcass development of beef cattle. A total of 64 steers were enrolled in this study over 2 years (32 steers/year), with 4 phases per year: creep-feeding (d 0 to 60), pre-weaning (d 61 to 120), post-weaning (d 121 to 180) and feedlot (181 to slaughter). On d 0 steers were ranked by body weight (BW) and age (114 ± 2 kg; 66 ± 0.5 d) and randomly assigned, in a 2 x 2 factorial, to receive 80 g/steer daily (creep-feeding) or 150 g/steer daily (post-weaning) of CSSO. Non-supplemented steers (CON) were provided with equivalent saturated fat supplement. On d 0, 61, 120, 180, and 330 steers were evaluated for longissimus muscle depth, backfat thickness, and marbling via real time ultrasonography, blood was sampled for determination of plasma fatty acid composition, muscle samples were collected via needle biopsy, and BW was recorded. After the creep-feeding phase, CSSO steers had greater (P < 0.01) plasma concentrations of linoleic, omega-6, and total PUFA compared with CON. Steers that received CSSO during the postweaning phase had greater (P < 0.01) plasma concentrations of linoleic, omega·-6, and total FA compared with CON prior to feedlot entry. No treatment differences were detected for performance or body composition responses (P > 0.25) during any phase. However, mRNA expression of adipogenic/lipogenic genes was greater (P < 0.03) prior to slaughter (d 330) in muscle of steers that had received CSSO during the creep-feeding phase. Results from this experiment suggest that supplementing CSSO to nursing beef steers via creep feeding stimulated metabolic imprinting effects through enhanced adipogenic gene expression, however did not alter phenotypic variables.